The effect of intellectual capital efficiency on Malaysian firm performance: a dynamic panel estimation / Znar Nahro Ahmed and Muhammad Rosni Amir Hussin - Ahmed, Znar Nahro; Amir Hussin, Muhammad Rosni (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
Even though reviews of intellectual capital (IC) and firm performance have been made, their role in developing markets has remained ambiguous. Prior research has typically concentrated on a particular industry while ignoring the contribution of the non-financial firms as a whole. This study aimed to investigate the influence of IC efficiency and firm performance in 11 industries of Malaysian non-financial firms. The study utilized panel data from 370 firms (1850 observations) listed in Malaysia from 2016 to 2020. The adjusted value-added intellectual coefficient (A-VAIC) model with new components (Relational and Innovation capital) was used to measure IC. This study applied a dynamic GMM approach to solve the issue of endogeneity and heteroscedasticity. The empirical findings revealed that IC efficiency was significantly and positively related to the performance of Malaysian listed firms. Moreover, three elements (human, relational and financial capital) positively influenced performance. Specifically, financial capital had the most influential component. The study will be beneficial to investors and policymakers on how IC investments improve performance. Also, the results of this study will help managers adopt new and innovative strategies to get ahead competitively among non-financial firms by using the IC as a premise.